Mechanochemical synthesis of intermetallic compounds in the system gallium – ruthenium - T. F. Grigoreva; E. A. Pavlov; P. A. Vitiaz; N. Z. Lyakhov (Chimica Techno Acta)
The interaction of a solid inert metal Ru with liquid active metal Ga during mechanical activation in a high-energy planetary ball mill was studied using the X-ray diffraction and the high resolution scanning electron microscopy with energy dispersive X-ray microanalyses. This paper considers mechanical activation effects on formation of intermetallic compounds GaxRuy and their solubility in concentrated acids. Gallium is a surface-active substance with respect to Ruthenium. Under intensive mechanical treatment, liquid Gallium penetrates into grain boundaries of polycrystalline Ruthenium particles and sharply reduces their strength. Because of severe mechanical deformation, an intensive increase of contact surface between solid and liquid metals observed, which a place of rapid formation of intermetallic compounds. This processing leads to high reactive products of mechanical activation of Ga + Ru. Their interaction with a mixed concentrated hydrochloric and nitric acid allows Ruthenium (~37%) to pass into an acidic solution, forming complex compounds of the HxRuCly type (H2RuCl6).